Unifying benefits of studies in legal pluralism: accessing actors' voices on human rights and legal pluralities in gender violence cases in India. Issue 3 (1st September 2016) - Relis, Tamara
ABSTRACT: Studies in legal pluralism have contributed to the framing and understanding of legal systems in the developing world. This article utilizes the conceptual framework of legal pluralism as an all embracing field in which the inter-connectedness of state and non-state laws can be more deeply explored, and through which grassroots realities including local actors' internalisation of international human rights laws can be analysed. In terms of "pluralism" this article examines some of the numerous units of non-state law or regulation operating on the ground in addition to or instead of formal state law. In this way, the role and contribution of studies in legal pluralism within the global North/global South debate becomes one that elucidates the resilience of non-state laws and norms in the face of contemporary global changes and state legal reforms. Working from a grounded theory paradigm, and drawing on the discourse of women victims of violence, accused and their families in eight states of India, the data presented here highlight various aspects of the limits of law's capabilities, the power of informal laws operating on the ground and the relationship of formal law with family and community non-state laws and norms. They further highlight how through the lens of legal pluralism, we can more clearly assess not only the actual workings of transnational human rights laws and domestic laws in compliance, but also the impact and internalisation of these laws by those whom they are designed to protect.